Electrochemical and spectroelectrochemical characterizations of new tetra-substituted metallophthalocyanines bearing 4-(trifluoromethoxy)phenoxy groups on non-peripheral positions - KOCA, ATIF (SPRINGER WIEN, 2020)
In this study, a series of non-peripherally tetra-substituted phthalocyanines [M = Zn(II), Co(II), and In(III)] was successfully prepared by cyclotetramerization of the phthalonitrile derivative bearing 4-(trifluoromethoxy)phenoxy group at 3-position. All newly synthesized compounds were characterized using spectroscopic methods, such as FT-IR, NMR, and UV-Vis spectroscopy. The effect of concentration on aggregation properties of the resulting phthalocyanines was investigated in different concentrations ranging from 4 x 10(-6)to 14 x 10(-6) M in THF. In addition, the spectral properties of the metallophthalocyanines were studied in various organic solvents. Besides, redox responses of metallophthalocyanines and their electro-optical responses were determined. Although {1(4),8(11),15(18),22(25)-tetrakis[4-(trifluoromethoxy)phenoxy]phthalocyaninato}cobalt(II) showed well-resolved reversible redox peaks depicting the anticipated electron transfer reactions, electrochemical investigation of its zinc(II) and indium(III) chloride analogs resulted in complex redox waves, and their chemical reversibility decreased with the aggregation of the complexes. The influence of the redox processes on the optical responses of metallophthalocyanines was studied with in situ spectroelectrochemistry measurements and the peak assignments and optical responses of the electrogenerated species were determined. [GRAPHICS] .
Keywords: Aggregation behavior; Electrochemistry; Phthalocyanine spectroelectrochemistry; 4-(Trifluoromethoxy)phenoxy; Non-peripherally; ZINC PHTHALOCYANINE; ANTIOXIDANT PROPERTIES; METAL-FREE; COBALT; MANGANESE; AGGREGATION; SEPARATION; COMPLEXES; BEHAVIOR